CONTEMPORARY ECONOMIC GROWTH AND THE CONSUMPTION OF ENERGY RAW MATERIALS (THE CASE OF SLOVENIA). - Križanič, France; Oplotnik, Zan (East European Quarterly)
The article discusses the economic growth and the consumption of energy raw materials in Slovenia. The major source of problems, encountered by the energy sector during transition from the infrastructural to a market oriented activity, is the specific nature of the energy raw materials market, with a long time-lag between a change in the dynamics of demand and the capacity of suppliers to adapt their production potential to this change.